Analisis Tingkat Kebisingan Akibat Aktivitas Kerja pada PT. A Gresik dengan Menggunakan Program Software Surfer - Rizka Novembrianto; Audyna Ayu Ramadhani (Prosiding ESEC, 2023)
Operational activities at PT. A have potential in the noise caused by the use of company tools. This noise greatly affects the employee's comfort at work and the environment around the company when the noise level exceeds the threshold value of noise. The purpose of this research is to determine the noise level, analyze the source of noise and provide solutions or suggestions for the control of such noise. The research method is performed by direct observation of the object using the Sound Level Meter (SLM) at 3 specified points and recording every 5 seconds for 5 minutes with the data obtained in decibels of ampere (dBA). The data will then be processed using the Surfer Software. The measurement results showed the noise level of PT. A at 3 points, namely 44,9 dB(A), 44,82 dB (A) and 55,31 dB(A). In the noise barrier effort that can be done by PT. A is to perform maintenance of the work equipment in the company on a regular basis so that the level of noise does not exceed the quality standards and the use of hearing protection in the workers.